THE USE OF ARTIFICIAL INTELLIGENCE IN THE DIAGNOSIS AND TREATMENT OF SEXUALLY TRANSMITTED SKIN DISEASES IN CHILDREN - Atakhanov Sanjarbek Anvarovich; Bahodirova Mohina Azizbek qizi (Bright Mind Publishing, 2025)
This article focuses on the diagnosis of sexually transmitted skin diseases in children and their positive and negative changes using artificial intelligence to reduce but make effective the latest clinical services and treatment dates provided to patients in the world during treatment.
Keywords: About AI, useful skin products, effective treatment, preliminary detection of tumors, advantages of artificial intelligence, the origin of skin diseases, skin damage caused by radioactive substances, laboratory skin biopsy and artificial intelligence testing.